KAWIN SEAR AFESER DI JEMAAT GMIT ELIM ALAANGLAH (KAJIAN SOSIO TEOLOGIS) - Gabriela Lodia Pulingmahi (Jurnal Ilmiah Sosiologi Agama (JISA), 2023)
The study used in this study is a socio-theological study, the sociological aspect that you want to examine, namely what are the social factors that cause the GMIT Elim Alaanglah Congregation to still maintain the sear afeser tradition and from a Christian theology perspective, it is assessed in the sear afeser tradition which is in line with the teachings Christianity This research uses a qualitative approach with the collection method carried out through in-depth interviews and observation. The findings of the data in the research are that the tradition of sear afeser is a tradition that has been passed down from generation to generation because it contains values of family unity and kinship, values of respect and cultural values. The sear afeser tradition contains sacred philosophical values through the symbolic act of holding hands to mark promises and commitments in building a once-in-a-lifetime household. The lack of understanding about the sanctity of the wedding blessing in the church is one of the causes of traditional marriage couples through the sear afeser tradition not continuing the confirmation and blessing of marriage in the church. sear afeser married couples understand that the confirmation and blessing of marriage in the church is only an administrative matter. For this reason, the church needs to proclaim a prophetic voice for couples who ignore the confirmation and blessing of marriage in the church so that married couples can reflect on their understanding and strengthen the foundation of their family life regarding the essence of Christian marriage